Factors Associated to The Occurrence of Stunting at The Primary Health Center in Madiun City, Indonesia - Arinaa Manasika Farida; Linda Dewanti; Ahmad Suryawan (Journal of Community Medicine and Public Health Research, 2024)
Stunting, a common nutritional problem characterized by a child's shorter stature due to growth failure, affects 11.5% of toddlers at Demangan Primary Health Center in Madiun, Indonesia. This research aimed to analyze factors linked to toddler stunting, using an observational analytical cross-sectional design. All toddlers visiting Demangan Primary Health Center's Integrated Health Post in Madiun were involved in the study sample. Maternal pre-pregnancy BMI, maternal upper arm circumference (LILA), maternal weight gain during pregnancy, inter-birth interval, low birth weight, per capita income, parental education, maternal knowledge on toddler's nutrition and parenting patterns of feeding were factors collected through questionnaires, Maternal and Child Health books, and primary health center records. Univariate and bivariate analysis results were tested using the Chi-Square or Fisher Exact test. In this study, 156 samples were obtained, consisting of 18 stunted toddlers (11.5%) and 138 normal toddlers (88.5%). Stunting associated with maternal pre-pregnancy BMI showed p=0.020, maternal upper arm circumference p=0.008, maternal weight gain during pregnancy pâ‰¤0.001, low birth weight p=0.001, per capita income p=0.007, and maternal knowledge on toddler's nutrition had p=0.011. In conclusion, pre-pregnancy conditions significantly influence stunting. So, enhancing interventions for maternal health during pre-pregnancy is crucial for maximizing impact.